2022
DOI: 10.24912/jm.v26i1.884
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing the Performance of Regional Government Apparatuses

Abstract: This study aims to examine and analyze the effect of Public Accountability, Decentralization Structure, Clarity of Budget Target and Managerial Roles of Regional Financial Managers on the Performance of Local Government Officials on Financial Managers of Regional Apparatus Organizations in Palu City. This is a quantitative study, and the data was gathered by a survey approach utilizing a questionnaire as the tool. Porposive sampling was used to obtain the sample, which included the head of the OPD and the head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Another problem faced by local governments is the lack of optimal regulation and security of regional property (Rahmayadi A, 2023). Regional property is all goods obtained or obtained using the regional budget (APBD) or derived from other legitimate acquisitions (PP Number 27, 2014;Susanto H, 2022;Pattawe A, 2022;Kartini, 2023), including goods obtained from donations/grants or the like, goods obtained as the implementation of contracts/agreements, goods obtained based on court decisions and goods obtained following the provisions of laws and regulations (Firmasyah A, 2020; Mandala, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another problem faced by local governments is the lack of optimal regulation and security of regional property (Rahmayadi A, 2023). Regional property is all goods obtained or obtained using the regional budget (APBD) or derived from other legitimate acquisitions (PP Number 27, 2014;Susanto H, 2022;Pattawe A, 2022;Kartini, 2023), including goods obtained from donations/grants or the like, goods obtained as the implementation of contracts/agreements, goods obtained based on court decisions and goods obtained following the provisions of laws and regulations (Firmasyah A, 2020; Mandala, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of local property such as vehicles, which are optimized by local governments to provide services to the community (Mandala, 2023). Local property is an economic resource owned by local governments that is expected to provide economic and social benefits in the future (Pattawe A, 2022). To prevent misuse of regional property management, it is the main thing to use effectively and efficiently public resources (Aneta Y, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an obligation that must be realized by the current government. Muliyati et al (2022) revealed that public accountability affects the performance of local government officials. The structure of decentralization affects the performance of local government officials, clarity of budget targets affects the performance of local government officials, and the managerial role of regional financial managers affects the performance of local government officials.…”
Section: Introductionmentioning
confidence: 99%